Effectiveness of sustainable palm oil education in improving knowledge of sustainable palm oil farming practices through game Sawit Palmi day series: A quasi-experiment on millennial and Zillennial generations in Jakarta - Sabrina, Stella; Sarwoprasodjo, Sarwititi; Fatchiya, Anna; Azahari, Delima Hasri (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the influence of the knowledge levels of the Millennial and Zillennial generations in Jakarta regarding sustainable palm oil, as well as their interest in learning about the topic before and after participating in the mobile-based educational game, “Game Sawit.” This study integrates Social Cognitive Theory and Gagne’s Conditions of Learning Theory. The Game Sawit serves as a medium to promote positive behavioral changes related to sustainable palm oil. It employs an edutainment strategy, combining education with entertainment. The study used a quasi-experimental design involving two experimental groups and a control group. The sample consisted of 120 participants, including 60 Millennials and 60 Zillennials. Data analysis was conducted using independent samples t-tests and paired t-tests. The results indicate that the Game Sawit significantly increased participants’ knowledge, especially in the experimental group that played the game, compared to the control group. This study has important implications for game-based educational campaigns aimed at improving knowledge and interest in sustainable palm oil among younger generations. The findings highlight the potential of digital edutainment in raising awareness of sustainable agricultural practices.